The Impact of Globalization on Economic Growth: Empirical Evidence from the Turkey - Kılıcarslan, Zerrin; Dumrul, Yasemin (International Journal of Economics and Financial Issues, 2018)
This article examines the impact of globalization on economic growth in Turkey covering the period from 1980 to 2015 using the globalization index and its components (economic, social and political globalization indices). For these sub-indices, the analyzes were repeated by making a distinction between “de facto” and “de jure”. According to the KOF overall globalization index, the result of the FMOLS co-integration test showed that economic growth increase "economic" and "social" globalization in Turkey. When KOF de facto and KOF de jure are separated, the effect of economic globalization on economic growth is negative and statistically insignificant. According to KOF de facto globalization index, social globalization increases economic growth, while in an analysis using the KOF de jure globalization index, social globalization reduces economic growth. Besides, political globalization negatively affects economic growth for all KOF globalization indices that are included in the analysis. Keywords: KOF globalization index, globalization, economic growth JEL Classifications: C32, F02, F43